Biopreservation of tomatoes using fermented media by lactic acid bacteria. (August 2020) - Luz, C.; D'Opazo, V.; Quiles, J.M.; Romano, R.; Mañes, J.; Meca, G.
Abstract: Post-harvest spoilage fungi in tomatoes represent an economic loss for industry and consumers. There is currently an increasing demand for novel applications of bio-preservatives as replacers of chemical additives and pesticides in food. In this study, nine lactic acid bacteria strains isolated from tomato and sourdough were screened for antifungal activity in vitro against 33 fungal strains and used as bio-preservatives of tomato inoculated with Penicillium expansum and Aspergillus flavus . The identification of the compounds potentially responsible for the antifungal activity, such as organic acids, phenolic acids and volatile organic compounds (VOCs), were identified and quantified. Several cell-free supernatants (CFS) showed in vitro antifungal activity against toxigenic fungi. The highest antifungal activity was observed in the CFS of Lactobacillus plantarum TR7 and L. plantarum TR71, these showed a range of MFC values of 6.3–100 g/L. Antifungal compounds were identified in CFS as organic acids, phenolic acids and VOCs. Lactic acid, acetic acid, phenyllactic acid and pyrazine derivatives can be related for the antifungal activity. Bio-preservation of tomato with the CFS fermented by L. plantarum TR7 and L. plantarum TR71 decreased the microbial count by 1.98–3.89 log10 spores/g in comparison to the treatment with medium non-fermented. Highlights: Antifungal activity of fermented media by LAB against toxigenic fungi. Identification of the bioactive compounds responsible of the antifungal activity. Improve shelf life of tomatoes using LAB as a novel biopreservation application.